Construction and validation of a nomogram for patients with pancreatic neuroendocrine tumors: A population study of 5,927 patients - Huang, Gaobo; Song, Weilun; Zhang, Yanchao; Ren, Bingyi; Lv, Yi; Liu, Kang (Frontiers in Gastroenterology, 2023)
Background Pancreatic neuroendocrine tumors (pNETs) are a group of uncommon tumors derived from peptide neurons and neuroendocrine cells, and account for roughly 2% to 4% of all pancreatic neoplasms. This study aimed to construct and validate a nomogram for predicting the prognosis of patients with pNETs. Our data came from the SEER database. Methods A total of 5927 pNETs patients between 2004 and 2018 were included in this study. The nomogram was constructed base on eight prognostic factors and validated by C-index, ROC curve and calibration curves. A nomogram based on eight independent prognostic factors (patient age, sex, race, tumor grade, AJCC T, AJCC N, AJCC M, surgery, radiation, chemotherapy, tumor function and marital status) was developed for the prediction of CSS at 3 and 5 years. Results The C-index and AUCs of the nomogram demonstrated that its superiority in discrimination over AJCC staging system. The calibration plots showed the good consistency between predictions and actual observations. Conclusions In conclusion, our nomogram could better predict the prognosis of pNETs patients than AJCC staging system. The nomogram could be improved by integrating more important factors other than SEER database.